Determinan Kinerja Keuangan : Peran Carbon Emission Disclosure (CED) dan Investment Opportunity Set (IOS) - Syafira Nur Lathifah; Tjahjaning Poerwati Poerwati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
The Healthcare sector plays a strategic role in improving public Health and quality of life, however, it also contributes to rising carbon emissions and environmental problems. This condition has increased demands on Healthcare companies not only to focus on financial performance but also to enhance transparency and environmental responsibility. This study aims to analyze the effect of Carbon Emission Disclosure (CED) and Investment Opportunity Set (IOS) on the financial performance of Healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports, with Purposive Sampling as the sampling technique. Data analysis is conducted using descriptive statistics, classical assumption tests, and multiple linear regression. The results indicate that Carbon Emission Disclosure (CED) has no significant effect on financial performance, while Investment Opportunity Set (IOS) has a significant effect on financial performance. These findings suggest that investment opportunities play an important role in improving the financial performance of Healthcare companies, while Carbon Emission Disclosure (CED) has not yet provided a direct impact on profitability.